Contextual factors related to aging determine force-based manipulation dosage: a prospective cross-sectional study. - Maiers, Michele J.; Sundin, Alexander R.; Oster, Ryan J.; Kreul, Steven; Malone, Quinn; Passmore, Steven R. (Chiropractic & Manual Therapies, 2025)
Background: Contextual factors influence clinicians' delivery of force-based manipulation (FBM), like spinal manipulative therapy (SMT). It is particularly important to discern how contextual factors interact with therapeutic forces delivered to an older adult population, to minimize risk and identify ideal dosage. This study aimed to determine whether contextual factors pertaining to aging result in the modulation of kinetic and kinematic parameters used by experienced clinicians when delivering SMT. Methods: Participants were randomly presented with a series of 12 AI-generated patient vignettes, featuring both visual and auditory content and representing varying age-related contextual factors. Factors included chronological (35-, 65- and 85-year-old), pathological ("healthy" vs degenerative spine), and felt (perceived as "young" vs. "old") age. Participants delivered SMT to a human analogue manikin based on each vignette, presented six times in randomized order. Kinetic and kinematic parameters were collected and analyzed for differences between "young" and "old" contextual factors of age, using a 3-way repeated measures ANOVA model. Results: Sixteen licensed chiropractors (8 female, 8 male) participated, with an average age of 45.4 (SD = 9.7, range 34–64) years and 18.3 (SD = 10.8, range 5–39) years of experience. A main effect in peak force was found for both chronological (F(2,30) = 26.18; p <.001, ηp2 = 0.636) and pathological age (F(1,15) = 11.58; p =.004, ηp2 = 0.436), following a stepwise progression of decreased force with increased age and with pathology. No statistically significant differences were found in peak force based on felt age, or in time to peak force for any factor. A main effect was found for chronological age with peak acceleration (F(2,20) = 9.50; p <.001, ηp2 = 0.487) and peak velocity (F(2,20) = 7.20; p =.004, ηp2 = 0.419), but not for pathological or felt age. There was a significant difference in time to peak velocity for felt age (F(1,10) = 12.23; p =.006, ηp2 = 0.550), with a shorter time to peak velocity in response to vignettes with older felt age. Conclusion: Contextual factors of aging modulated certain kinetic and kinematic characteristics when delivering SMT. This provides evidence that practitioners differentially discern aspects of aging to inform how they deliver FBM dosage. Future research is needed to identify ideal kinetic and kinematic characteristics based on considerations of aging.